Formulasi Lotion Sari Buah Mangga (Mangifera Indica L.) Sebagai Pelembab Kulit - Karphiawati, Aldilla Shalsa; Zuniarto, Ahmad Azrul; Pandanwangi TW, Siti; Karsidin, Bambang; Nafi'ah, Rahma; Zakiah, Fitri; Dewi, Komala (Jurnal Farmasi & Sains Indonesia, 2024)
Making mango juice lotion (Mangifera indica L.) using various concentration variations is expected to produce mango juice lotion (Mangifera indica L.) which meets the requirements for a good lotion and tests skin moisture against the mango juice lotion formula (Mangifera indica L.). This study aims to determine the best concentration of mango (Mangifera indica L.). In this study, mango juice was obtained by extortion, made in the form of lotion and tested for skin moisture using a Skin Analyzer. Data analysis in the form of SPPS (Statistical Product and Service Solution) tables. The results showed that the addition of the concentration of mango juice (Mangifera indica L.) had an effect on the resulting skin moisture. The selected formula of Mango juice lotion (Mangifera indica L.), namely formula 1 with a concentration of 5%, has a skin moisture value of 70,55%, and Mango fruit juice lotion (Mangifera indica L.).